INSTAGRAM REELS SEBAGAI MEDIA DALAM MENULIS TEKS PROSEDUR UNTUK SISWA KELAS 9 SMP N 1 PAGERUYUNG TAHUN AKADEMIK 2021/2022 - Nanda Rizky Saputri (Dharmas Education Journal (DE_Journal), 2021)
Abstract There are two objectives of the study, the objectives are (1) To find the students’ improvement in writing procedure text before and after being taught by using Instagram Reels, (2) To know the students’ response the use of Instagram Reels in writing teaching learning process. The methodology of the study is pre-experimental Study. The writer used one group pre – test and post – test. The data were gathered through quantitative data. The writer took 30 students. The result of this study showed that: (1) The score of the students’ before using Instagram Reels in writing skills of procedure text has average 62.6 and the score of the students’ after using Instagram Reels in writing skills of procedure text has average 82. The value of sig. (2-tailed) was 0.00. if the value sig (2-tailed) between the score of pre – test and post – test was 0.000<0.050 means that there was significant difference between the students’ score before and after using Instagram Reels. (2) Most students responded positively to the use of Instagram Reels to improve their interest in writing, and they could be more creative in writing procedure text.